Translating growth into poverty reduction : beyond the numbers - Kessy, Flora L.; Mashindano, Oswald; Shepherd, Andrew; Scott, Lucy (Research officer)
Tanzania is a politically stable, much aided country that has consistently grown economically during the first decade of the millennium, while also improving its human development indicators. However, poverty has remained persistent, particularly within rural areas. This collaborative work delves into the reasons why this is so and what can be done to improve the record. The book is the product of both Tanzanian and international poverty experts, based on largely qualitative research undertaken within Tanzania by the Chronic Poverty Research Centre (CPRC). The authors highlight and discuss the